TON1 and FASS are required to recruit myosin VIII, a cell division guidance factor - Shu-Zon Wu; Darren R. Mallett; Samantha E. Ryken; Magdalena Bezanilla (Proceedings of the National Academy of Sciences, 2026)
Because plant cells cannot migrate, their position is fixed with respect to their neighbors. Thus, placement of the new cell plate is critical for determining cell shape, cell identity, and tissue patterning. Here, we show that TONNEAU1 (TON1), a protein essential for preprophase band formation, plays a role in phragmoplast guidance even in cells that do not have a microtubule-based preprophase band. TON1 is part of a complex that contains TONNEAU2/FASS, PROTEIN PHOSPHATASE 2A (PP2A), and the TON1 RECRUITING MOTIF (TRM) proteins, known as the TON1-TRM-PP2A (TTP) complex. We found that TON1 localizes specifically to the plasma membrane along the branch-adjacent wall in a branching cell in Physcomitrium patens juvenile tissue. Knocking out FASS does not affect TON1 localization, suggesting that TON1 recruitment to the plasma membrane is independent of FASS. A novel point mutation in TON1 disrupts dimerization and localization to the plasma membrane. In mutants lacking TTP function, myosin VIII localization is altered, resulting in phragmoplast guidance defects. Our data suggest a model whereby myosin VIII guides the phragmoplast in a TTP-dependent manner to the branch-adjacent wall facilitating efficient insertion at that site.